Сlinical manifestations, diagnostics and therapy of herpetic keratitis today: three facets of one problem - G. M. Chernakova; D. Yu. Maychuk; T. B. Semenova (Российский офтальмологический журнал)
This article presents modern aspects of clinical manifestations, laboratory diagnostics and treatment of herpetic keratitis (HK). A total of 68 patients participated in the study. In 75 percent of patients high relapse rates of Herpes Simplex skin infection were revealed in the period before HK onset (one-six times per year). Trigger factors for keratitis were thoroughly analyzed. Among them we discovered a number of new ones: the instillation of prostaglandin analogues, paranasal sinus surgery, septoplasty and blepharoplasty. 51 out of 68 patients had active herpetic keratitis, whereas 17 people were in the remission phase. Polymerase chain reaction (PCR) test results for the herpes viruses (HSV, VZV, CMV, EBV, HHV-6) in various body fluids (tears, saliva, blood and urine) from patients with HK are discussed. Herpesvirus DNA was determined in 96 percent of cases (49 out of 51 patients with active HK). Among these 49 patients a monoinfection was detected in 47 percent of cases and mixed infection - in 53 percent. According to the obtained results, we proposed some optimized treatment solutions // Russian Ophthalmological Journal, 2017; 1: 90-7. doi: 10.21516/2072-0076-2017-10-1-90-97.